Evaluation of Integrated Records Information System (SRIKANDI) Version 3 As An Electronic Records Management System (ERMS): ISO 16175-2:2011 Creation Aspect - Novelawaty, Yeni Dwi; Herawan, Lufi (UI Scholars Hub, 2024)
This study aims to evaluate the Integrated Record Information System application (SRIKANDI) version 3, which is an Electronic Records Management System (ERMS), guided by ISO 16175-2:2011, particularly focusing on the aspect of creation. This study utilizes the method of descriptive qualitative by a literature study approach and direct observation of the SRIKANDI application. The research methodology includes preparation, conducting evaluations based on ISO 16175-2:2011, managing evaluation results, and drafting conclusions/findings. The evaluation examines several aspects, including the processes of capture, metadata capture point, aggregation digital record, importing of bulk, the formats of digital document, compound records, identification, classification schemes, and record volumes. The evaluation results indicate that the SRIKANDI application meets most of the criteria set by ISO 16175-2:2011. However, some aspects still require improvement, particularly in terms of email integration. These findings provide a foundation for the future development and enhancement of the SRIKANDI application, especially in managing electronic records within central and regional government environments.